DOI: 10.18297/etd/2103
|View full text |Cite
|
Sign up to set email alerts
|

Support partners of registered sex offenders : exploring their experiences, identities, and perceptions.

Abstract: Although it is widely recognized that many convicted criminal offenders experience considerable setbacks in communities that make their lives more arduous, registered sex offenders (RSOs) who live in American society arguably face more challenging impediments. As a result, ensuring their access to social support is especially salient. The notion that social support is particularly relevant to RSOs is perhaps best manifested through a common feature of community-based sex offender treatment programs, where part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 125 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…In addition, a number of collateral consequences have been identified for SORN. Included among these are that many RSOs rely heavily on supportive family members for stability in the areas of housing, financial, and social support (Burchfield & Mingus, 2008; Conner, 2015; Tewksbury & Levenson, 2009). This extension of collateral consequences is supported by our findings showing 35.6% of the respondents currently living with a family member.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a number of collateral consequences have been identified for SORN. Included among these are that many RSOs rely heavily on supportive family members for stability in the areas of housing, financial, and social support (Burchfield & Mingus, 2008; Conner, 2015; Tewksbury & Levenson, 2009). This extension of collateral consequences is supported by our findings showing 35.6% of the respondents currently living with a family member.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the literature, sex offenders' housing obstacles have been well documented (see Mustaine, Tewksbury, & Stengel, 2006;Ragusa-Salerno & Zgoba, 2012;Tewksbury, Mustaine, & Rolfe, 2016). Previous studies have also found that family members are treated similarly to the sex offender they house (Conner, 2015;Farkas & Miller, 2007;). Yet very little research has addressed any specific association of sex offenders living with family members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation